The mediating role of health anxiety on the relationship between health literacy, death anxiety and quality of life - Mahmoud Mohammadi; Azadeh Choobforoushzadeh; Yasser Rezapour Mirsaleh; Elahe Shirovi (پژوهشنامه روانشناسی مثبت)
The present study was conducted with the aim of investigating the mediating role of health anxiety on the relationship between health literacy, death anxiety and quality of life. The research method was descriptive-correlation and structural equation modeling. The statistical population was all the students of Ardakan University in the academic year of 2013-2014, and 334 of them were selected using available sampling method. To collect data, Health Literacy Questionnaire of the Urban Population of Iran, Health Anxiety Questionnaire, Death Anxiety Questionnaire and World Health Organization's Quality of Life Questionnaire SF-36 were used. The findings showed that health literacy and death anxiety have a direct and significant effect on quality of life, health literacy on health anxiety, and death anxiety on health anxiety. Health literacy and death anxiety influence quality of life through the mediation of health anxiety. From the findings of the present research, we can understand the necessity of improving the level of health literacy to improve the quality of life and mental health.IntroductionQuality of life is defined as people's perceptions of their position in life within the framework of culture and value system, their expectations, standards and concerns in relation to their goals (Bobes et al., 2022) and can be influenced by factors such as self-efficacy, psychological well-being, health literacy (Söğütlü & Göktaş, 2021), death anxiety and disease perception (Majared, 2018) and health anxiety (Hayter et al., 2016). Death anxiety includes motivational, cognitive and emotional components, changes under the influence of growth stages, events of social and cultural life (Elisabeth, 2020). On the other hand, heath literacy includes a set of reading, listening, analysis and decision-making skills and the ability to use these skills in health situations (Parker & Ratzan, 2019). Health anxiety means creating worry and anxiety when health is threatened. It is defined as a spectrum from ignorance about health to extreme health anxiety or self-morbidity (Bailer et al., 2016). Elizabeth (2020) showed that health literacy is important for both quality of life and long-term treatment adherence. Owen et al. (2020) believe that reducing death anxiety is an important goal in terms of therapeutic intervention to improve the quality of life. The consequences of lack of health literacy are death anxiety and poor quality of life and poor performance of physical and mental health in people. This study examines the mediating role of health anxiety in the relationship between health literacy and death anxiety with quality of life. MethodThe current research design was of a descriptive-correlation type. The statistical population included all the students of Ardakan University in the year 1400, who were selected due to the special conditions of the society (COVID19 pandemic) with the available sampling method. Inclusion criteria included the following: absence of any chronic physical illness (according to student self-report) and informed consent. The exclusion criteria were: incomplete answers in the questionnaire. Questionnaires were designed online and distributed through social networks (Telegram and WhatsApp) in student groups of Ardakan University. Iranian health literacy questionnaire (HELIA), death anxiety questionnaire, health anxiety questionnaire and quality of life questionnaire were used. Answering the questions was completely voluntary and they could withdraw from the study whenever they wanted. The participants could be informed about the results of their study and questionnaire if they wish. Path analysis method was used for data analysis with the help of SPSS version 24 and AMOS version 24 software. ResultsThe results showed that health literacy had a significant positive relationship with quality of life, death anxiety and health anxiety had a negative and significant relationship with quality of life.  Table1Values of Structural Equation Model Generality Evaluation Indicesχ2 /dfIFIGFITLICFINFIP2.920.90.90.90.90.9<0.05   According to the value of the model fit evaluation indices in Table 1, it can be concluded that the model fit the data well.  Table2Direct Effects between Research Variables PT S.EDependentvariableIndependentvariable 0.000.000.005.26-3.86-8.170.24-0.2-0.40.060.160.09 Quality of life Health literacyDeath anxietyHealth anxiety  Table 2 shows that all relationships between variables were significant at the  95% confidence level according to T values ​​(P<0.05).  Table3 Indirect Effects between Research Variables(P-Value of Bootstrap)S Dependentvariable MediationIndependentvariable0.0020.08 Quality of Life Health anxietyHealth literacy0.001-0.22  Death anxietyThe results of the bootstrap analysis showed that health literacy and death anxiety affected the quality of life through health anxiety, and its indirect coefficients were 0.08 and 0.22, respectively. Thus, the evaluation of the indirect effect using the bootstrap method showed that the indirect effect of health literacy and death health on quality of life was mediated by health anxiety. DiscussionThe aim of the present study was to analyze the effects of health literacy and death anxiety on quality of life, considering the role of the mediating variable of anxiety on Ardakan University students. The results showed that the variable of health literacy had a positive relationship with quality of life. This finding is in line with the results of researches (Elisabeth, 2020; Nilsen et al., 2020; Zheng et al., 2018). The results showed that death anxiety had a negative and significant relationship with quality of life. This finding is in line with the results of (Onu et al., 2020; Park et al., 2013). The results showed that health anxiety has a negative and significant relationship with quality of life. This finding is in line with the results of (Abdelghani et al., 2021; Eraslan & İlhan, 2023; Hayter et al., 2016). The results showed that health anxiety mediated the relationship between health literacy and death anxiety with students' quality of life. Death has inevitable fear and excitement, and because no one has experienced or touched it, thinking about it causes anxiety (Onu et al., 2020). Death anxiety includes a set of attitudes towards death such as threat, fear, worry, discomfort and other negative emotional reactions with anxiety that affect mental health (Bowling, 2017). Therefore, reducing the anxiety of death reduces anxiety about people's health, and this reduction of anxiety causes vitality, activity and freshness in their lives.One of the limitations of the current research is that the current research design was conducted on the student community. It is suggested to conduct a similar research for other sections of society to confirm and complete the results.  Consideration EthicalCompliance Whit Ethical Guidelines: All ethical issues such as informed consent and confidentiality of participant’s identity were respected.Author of Contributions: All authors contributed to the study. The first author wrote the first draft of the manuscript. The second and third authors edited the manuscript and the second author is corresponding author.Conflict of Interest: The authors declare no conflict of interest for this study.Funding: This study was extract from the thesis of the master's course and conducted with no financial support.Acknowledgment: The author thanks all participants in the study.           *. Corresponding author